Analisis faktor penyebab tingkatan gangguan Low Back Pain (LBP) pada pengrajin daun nipah di Kelurahan Terjun Kecamatan Medan Marelan - Aprisandi, Ageng; Silaban, Gerry (TROPHICO, 2023)
Low Back Pain (LBP) is pain the lower back from spiral spine (lower back), nerves and muscles caused by giving heavy workload and long duration thereby resulting in excessive muscle contractions. This study to see relationship factors cause complaints Low Back Pain (LBP) in palm leaf craftsmen in Kelurahan Terjun Kecamatan Medan Marelan. This research used cross sectional design that involved 35 nipah leaf craftsmen who were obtained by total sampling technique. This study uses chi square test to see relationship between individual factors and occupational factors with complaints Low Back Pain (LBP). The level complaints Low Back Pain (LBP) uses Oswestry Disability Index (ODI) questionnaire measurement. The results of this study was found that 35 palm leaf craftsmen who felt complaint Low Back Pain (LBP), 28 palm leaf craftsmen experienced a minimum disturbance (80%) while with moderate disturbances were 7 palm leaf craftsmen (20%). Based on results statistical tests, it was found that age (p=0.016), working period (p=0.001), and working posture (p=0.000) had a relationship with complaints Low Back Pain (LBP) in palm leaf craftsmen.Palm leaf craftsmen are advised to adjust their working time, muscle stretching movements between work and use work aids such as chairs and tables so that complaints Low Back Pain (LBP) can be minimized and prevented.